Monoamine metabolites in cerebrospinal fluid in multiple sclerosis. Issue 8 (August 1977) - Davidson, D; Pullar, I A; Mawdsley, C; Kinloch, N; Yates, C M
Abstract : The concentrations of homovanillic acid (HVA), 5-hydroxyindolylacetic acid (5-HIAA), and 4-hydroxy, 3-methoxyphenylethylene glycol (MHPG) were estimated in the lumbar cerebrospinal fluid (CSF) of control subjects and in some patients who probably, and others who definitely, suffered from multiple sclerosis (MS). In the control group, the concentration of HVA was lower in people who underwent lumbar puncture having fasted and been recumbent for 12 hours before the procedure than in those from whom CSF was obtained under non-standardised conditions. These studies demonstrate that a standardised procedure for lumbar puncture is required in order to obtain meaningful results. In patients suffering from MS the CSF 5-HIAA concentrations were significantly lower than in comparable controls but the HVA concentrations did not differ. There was no relationship between metabolite concentrations, site of lesion, the duration of the disease, gamma-globulin levels nor the occurrence of relapse within the previous month.